2016
DOI: 10.1186/s12890-016-0231-3
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective analysis to identify predictors of COPD-related rehospitalization

Abstract: BackgroundChronic obstructive pulmonary disease (COPD) is often associated with recurrent hospitalizations. This study aimed to identify factors related to COPD rehospitalization.MethodsA national US claims database was used to identify patients, aged ≥40 years, hospitalized for COPD. Their first COPD-related hospital admission date in 2009 was set as the index date, with post-discharge COPD-related rehospitalization assessed for 180 days post-index date. Data were analyzed for: 1) all eligible patients in who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 22 publications
2
30
1
Order By: Relevance
“…We have observed a reduction in readmission rates at 30, 60, and 90 days for both all-cause and COPD-related admissions. However, our failure to show a benefit in COPD-related readmission at 30 days admissions is consistent with other studies that have shown a similar readmission rate at this time point 28,29. One potential factor is that as we reduce the LOS, there is a risk of premature discharge of subjects who even with intensive community supports fail to transition to a stable clinical state at home.…”
Section: Discussionsupporting
confidence: 89%
“…We have observed a reduction in readmission rates at 30, 60, and 90 days for both all-cause and COPD-related admissions. However, our failure to show a benefit in COPD-related readmission at 30 days admissions is consistent with other studies that have shown a similar readmission rate at this time point 28,29. One potential factor is that as we reduce the LOS, there is a risk of premature discharge of subjects who even with intensive community supports fail to transition to a stable clinical state at home.…”
Section: Discussionsupporting
confidence: 89%
“…Patients who received physician follow-up within 30 days of discharge were significantly less likely to be readmitted (OR 0.7; P <0.001) 16. Roberts et al (2016) conducted a study involving 3,612 COPD admissions, and reported that comorbidities and prior hospitalizations were the strongest predictors of early COPD-related rehospitalizations (<30 days), while respiratory-related therapies including the use of steroids (OR 1.62, P =0.007) and nebulizers (OR 1.65, P =0.007) during the index admission were the strongest predictor of late COPD-related re-hospitalizations (>30 days), but not early rehospitalizations 17. Similarly, several studies have indicated that patients prescribed steroids and antibiotics were less likely to be readmitted 1821…”
Section: Discussionmentioning
confidence: 99%
“…Patients admitted with an exacerbation experienced a marked decline in their lung function, worse quality of life and shorter survival [3,6,23]. In addition, hospitalized COPD patients have an increased risk of new hospital readmission [4,5]. Previous studies have identified "frequent exacerbator phenotype," which is independent of disease severity, defined as those COPD patients who had 2 or more exacerbations [9].…”
Section: Discussionmentioning
confidence: 99%
“…Patients admitted with an exacerbation have an increased risk of future hospital readmissions [4,5], which is also related with a progressive increase in the risk of death [6]. Therefore, COPD patients with frequent hospitalized exacerbations (FHE) are a population with important clinical and social implications [7,8].…”
Section: Introductionmentioning
confidence: 99%